2016
DOI: 10.1111/jocn.13423
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between breastfeeding self‐efficacy and LATCH scores and affecting factors

Abstract: It is of great importance that midwives and obstetric nurses routinely evaluate breastfeeding self-efficacy and the capability of breastfeeding for early detection of problems related to breastfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 50 publications
2
28
0
11
Order By: Relevance
“…Evidence suggests that women with a higher sense of BFSE have higher rates of breastfeeding initiation, longer durations of any breastfeeding, and longer durations of exclusive breastfeeding, as compared to women who report a lower sense of BFSE (Table 3) (Gercek et al, 2017; Henshaw et al, 2015; Karall et al, 2015). Additionally, two qualitative studies that examined mothers’ decisions to breastfeed identified self-efficacy as an important theme (Barbosa et al, 2017; Furman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that women with a higher sense of BFSE have higher rates of breastfeeding initiation, longer durations of any breastfeeding, and longer durations of exclusive breastfeeding, as compared to women who report a lower sense of BFSE (Table 3) (Gercek et al, 2017; Henshaw et al, 2015; Karall et al, 2015). Additionally, two qualitative studies that examined mothers’ decisions to breastfeed identified self-efficacy as an important theme (Barbosa et al, 2017; Furman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Mothers who reported a higher sense of BFSE had higher rates of breastfeeding initiation and a longer duration of any breastfeeding including exclusive breastfeeding (Gercek et al, 2017; Henshaw et al, 2015; Karall et al, 2015). The association of self-efficacy with breastfeeding was also supported by studies describing how interventions that increase a mother’s sense of BFSE are successful at increasing the duration and exclusivity of breastfeeding (Abbass-Dick et al, 2017; Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, Gercek et al, and Sowjanya et al, tried to study the correlation of the LATCH score and BSES-SF scale. 4,7 Gercek et al, found a weak positive correlation but Sowjanya et al, found a strong positive correlation between the two and thus concluded that LATCH score and BSES-SF can be used as assessment tools at delivery in all hospitals to assist in identifying and targeting mothers at risk of early weaning in order to improve the breast feeding duration as well as confidence in the mothers as they are simple, reliable and cost effective. Whereas, in this study, author haven't utilized any other assessment tool apart from LATCH scoring.…”
Section: Discussionmentioning
confidence: 99%
“…(23) Another recent study comparing LATCH with a known self-efficacy instrument -short version (BSES-SF) demonstrated a positive correlation between instruments in postpartum women. (24) Therefore, the relevance of the present study is being the first to perform the scale cultural adaptation in South America, which will impact positively on its use by the Brazilian population given its benefits, mainly in relation to its practicality. This was confirmed during the LATCH scale application in clinical practice by nurses of this study.…”
Section: Discussionmentioning
confidence: 99%